(untitled) (Tejganga Darpan, 2026)
The process of teaching and learning may be seen as the conveyance of knowledge and proficiency from teachers to students. A combination of multiple parts is the term used to describe the process through which a teacher identifies and creates the learning goals, prepares instructional materials and puts the teaching and learning strategy into action. Nevertheless, education is a field one must consider the most crucial aspect of learning. In order to determine whether or not teaching at the higher education level is adequate, the objective of this research was to conduct a literature search on pedagogy, inclusive practices, and a variety of academic publications. This research aims to assess the teaching abilities of professors working in higher education settings. The study analyzed the theory by using literary genres and experimental research procedures (mostly introspection) while also attempting to strengthen the practice via university experiences. The study’s findings indicate that providing students with constructive and suitable feedback for development and the opportunity to participate in role playing activities has a significant and positive impact on the levels of confidence and self-esteem that student’s exhibit. Additionally, it was shown that an inclusive atmosphere encourages inclusivity and improves the academic success of both students and teachers.